AGRICULTURAL INNOVATION AND ITS IMPACT ON FARMERS' ECONOMIC WELFARE: A CASE STUDY IN AGRO DIGITAL TASIKMALAYA - ita Minarti; Rina Nurul Azmi; Ade Sri Rahmatilah; Rendi Septiansyah; Firza Ikhsan Mediansyah; Yani Sri Astuti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research explores the impact of agricultural innovation on the economic welfare of farmers in Agro Digital Tasikmalaya. The main challenges for the agricultural sector in Indonesia include low productivity and dependence on traditional methods. Innovation through modern technology and digitalization is a solution to increase productivity and market access. Agro Digital Tasikmalaya integrates agriculture, tourism and digital marketing, enabling farmers to sell products directly to consumers via social media. The results show increased productivity, income and market access for farmers. This research uses qualitative methods with primary and secondary data, as well as observations and interviews. Agro Digital Tasikmalaya plays an important role in creating an efficient and sustainable agricultural ecosystem, as well as providing training to farmers. Despite this, challenges such as access to subsidized fertilizer and lack of human resources, especially the younger generation, still exist. Solutions require a comprehensive approach from the government, private sector and educational institutions to improve fertilizer distribution and attract the younger generation to the digital agricultural sector.